Pathological hypertrophy and cardiac dysfunction are linked to aberrant endogenous unsaturated fatty acid metabolism - De Tomasi, Loreta Casquel [UNESP]; Salome Campos, Dijon Henrique [UNESP]; Sant'Ana, Paula Grippa [UNESP]; Okoshi, Katashi [UNESP]; Padovani, Carlos Roberto [UNESP]; Murata, Gilson Masahiro; Nguyen, Son; Kolwicz, Stephen C.; Cicogna, Antonio Carlos [UNESP] (Public Library Science, 2018)
Pathological cardiac hypertrophy leads to derangements in lipid metabolism that may contribute to the development of cardiac dysfunction. Since previous studies, using high saturated fat diets, have yielded inconclusive results, we investigated whether provision of a high-unsaturated fatty acid ( HUFA) diet was sufficient to restore impaired lipid metabolism and normalize diastolic dysfunction in the pathologically hypertrophied heart. Male, Wistar rats were subjected to supra-valvar aortic stenosis ( SVAS) or sham surgery. After 6 weeks, diastolic dysfunction and pathological hypertrophy was confirmed and both sham and SVAS rats were treated with either normolipidic or HUFA diet. At 18 weeks post-surgery, the HUFA diet failed to normalize decreased E/A ratios or attenuate measures of cardiac hypertrophy in SVAS animals. Enzymatic activity assays and gene expression analysis showed that both normolipidic and HUFA-fed hypertrophied hearts had similar increases in glycolytic enzyme activity and down-regulation of fatty acid oxidation genes. Mass spectrometry analysis revealed depletion of unsaturated fatty acids, primarily linoleate and oleate, within the endogenous lipid pools of normolipidic SVAS hearts. The HUFA diet did not restore linoleate or oleate in the cardiac lipid pools, but did maintain body weight and adipose mass in SVAS animals. Overall, these results suggest that, in addition to decreased fatty acid oxidation, aberrant unsaturated fatty acid metabolism may be a maladaptive signature of the pathologically hypertrophied heart. The HUFA diet is insufficient to reverse metabolic remodeling, diastolic dysfunction, or pathologically hypertrophy, possibly do to preferentially partitioning of unsaturated fatty acids to adipose tissue.